An economic analysis method for ship charging and swapping station in smart grid - Zhou, Ligang; Qiu, Tiejun; Rong, Yanhai; Peng, Shuang; Li, Wei; Xie, Longjie (Frontiers in Energy Research, 2025)
The reliable power supply and economic analysis of ship charging and swapping station are crucial for promoting the electrification of the shipping industry and achieving the dual carbon goals. This paper focuses on the development of an economic analysis method for ship charging and swapping stations within smart grid application scenarios. Firstly, the cost model is established by considering the construction, operation, maintenance, and equipment replacement of ship charging and swapping stations. Secondly, an operational model is defined, outlining the constraints for charging and discharging processes as well as backup power capabilities. Thirdly, an economic analysis framework is developed to minimize total investment and operational costs, incorporating factors such as thermal power unit operation, wind power curtailment, and deep peak shaving of thermal units. Finally, the proposed models are validated through a case study using modified IEEE 9-bus and IEEE 30-bus systems, and the results demonstrate significant improvements in economic efficiency and system performance when incorporating ship charging and swapping station.